Macrophage migration inhibitory factor regulates innate γδ T‐cell responses via IL‐17 expression. Issue 6 (28th February 2019) - Kim, Hee Kyung; Garcia, Alvaro Baeza; Siu, Edwin; Tilstam, Pathricia; Das, Rita; Roberts, Scott; Leng, Lin; Bucala, Richard
ABSTRACT: T cells expressing invariant γδ antigen receptors (γδ T cells) bridge innate and adaptive immunity and facilitate barrier responses to pathogens. Macrophage migration inhibitory factor (MIF) is an upstream mediator of host defense that up‐regulates the expression of pattern recognition receptors and sustains inflammatory responses by inhibiting activation‐induced apoptosis in monocytes and macrophages. Surprisingly, Mif −/− γδ T cells, when compared with wild type, were observed to produce >10‐fold higher levels of the proinflammatory cytokine IL‐17 after stimulation with gram‐positive exotoxins. High‐IL‐17 expression was associated with the characteristic features of IL‐17‐producing γδ T (γδ17) cells, including expression of IL‐23R, IL‐1R1, and the transcription factors RORγt and Sox13. In the gram‐positive model of shock mediated by toxic shock syndrome toxin (TSST‐1), Mif −/− mice succumbed to death more quickly with increased pulmonary neutrophil accumulation and higher production of cytokines, including IL‐lβ and IL‐23. Mif −/− γδ T cells also produced high levels of IL‐17 in response to Mycobacterium lipomannan, and depletion of γδ T cells improved survival from acutely lethal Mycobacterium infection or TSST‐1 administration. These data indicate that MIF deficiency is associated with a compensatory amplification of γδ17 cell responses, with implications for innate immunity and IL‐17‐mediated pathology in situations such as gram‐positive toxic shock or Mycobacterium infection.—Kim, H. K., Garcia, A. B., Siu, E., Tilstam, P., Das, R., Roberts, S., Leng, L., Bucala, R. Macrophage migration inhibitory factor regulates innate γδ T‐cell responses via IL‐17 expression. FASEB J. 33, 6919–6932 (2019). www.fasebj.org